Монгол оюутнуудын aнгли хэлний эгшиг авианы дуудлагын алдаанд хийсэн дүн шинжилгээ: An Error Analysis of The English Vowels Produced by Mongolian Students - Ts., Oyunsuren; R., Batsuren (Mongolian Journal of Foreign Languages and Cultures, 2023)
The purpose of the present research study was to carry out an error analysis on the English vowel production by a cohort consists of 94 Mongolian intermediate level students. In this respect, we investigated the errors in a corpus of 94 versions of the speech produced by the intermediate students of the School of Arts and Sciences at NUM. All the errors related to the English vowel production in this article were identified, described, explained and evaluated according to Heidi Dulay, Marina Burt and Stephen Krashen’s taxonomy. Specifically, we aimed to identify the source of the errors. The findings demonstrated that the source of students' errors could be explained by interlingual and intralingual transfers. Furthermore, we wrote a recommendation for the students to improve their pronunciation.